Identifikasi Kesalahan Siswa dalam Menyelesaikan Soal Numerasi: Tinjauan melalui Kerangka Teori Nolting - Putri, Amalia; Basir, Mochamad Abdul (Universitas PGRI Semarang, 2025)
This study aims to identify errors made by students in solving numeracy literacy problems on probability material and to find out the factors that cause these errors. The type of research conducted is descriptive qualitative research. Data collection techniques include observation, written tests, and interviews. The subjects of this research were 6 students of class X-2 SMA Islam Sultan Agung 3 Semarang. The instruments used in this research are 2 questions of numeracy literacy description of probability material. Data analysis was carried out using the stages of data reduction, data presentation, and conclusion drawing. Data validity technique is done by comparing data from interviews obtained from each subject or called source triangulation. The results showed that there were 6 errors in solving numeracy literacy problems based on Nolting's theory: misread-direction, careless, concept, application, test-taking, and study errors. The highest form of student error is in the category of test-taking errors, where students do not write conclusions, and some students write incorrect conclusions. The factors causing this are that students are less careful during the process of applying the problem, and are too hasty in working on the problem.